PEMILIHAN KRITERIA PEMASOK DENGAN PENDEKATAN FUZZY-ANP PADA INDUSTRI SARUNG TANGAN: Array (Universitas Harapan Medan, 2019)
Supplier plays an important role in the availability of raw materials for the ongoing production activities of a company. The selection of the right supplier can significantly reduce the cost of purchasing the company and consequently increase the competitiveness of the company. This study aims to analyze the selection of suppliers (suppliers) of soap raw materials at PT. Shamrock Manufacturing Corpora Medan with the approach of Fuzzy Analytic Network Process (FANP) Data obtained by interviewing techniques and filling out questionnaires from samples determined by Judgment sampling. Data analysis using the Fuzzy Analytic Network Process (FANP) approach, obtained results that the supplier of raw materials (suppliers), namely PT. Sei Rahayu Agung (Aek Kanopan), which weighs 0.316, second place is PT. Maja Agung (Rantau Prapat) with a weight of 0.310, the third position is DS-Salak (Kisaran) with a weight of 0.237, and the last is SG-Makmur (Rantau Prapat) with a weight of 0.184. The FANP method for selecting raw material suppliers can be applied by PT. Shamrock Manufacturing Corpora Medan as a reference in the company's development decision support system.